2019
DOI: 10.1111/nin.12332
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating the gendered nature of health‐promoting activities among nursing staff in forensic psychiatric care

Abstract: When people in Sweden are sentenced and handed over to forensic psychiatric care (FPC), the authorities have overall responsibility for their health recovery. How nursing staff construct gender through their relations in this context affects their understanding of health promotion activities. The aim of this study was to illuminate, using a gender perspective, the understanding of nursing staff with respect to health promotion activities for patients. Four focus group interviews were conducted with nursing sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Along those lines, a remarkable finding was that the staff seldom reported physical violence among the patients, although most of them had been committed to forensic care for perpetrating violent crimes. It is also interesting in relation to other studies were staff talk about patients as not trustworthy and violent (Kumpula et al, 2019).…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…Along those lines, a remarkable finding was that the staff seldom reported physical violence among the patients, although most of them had been committed to forensic care for perpetrating violent crimes. It is also interesting in relation to other studies were staff talk about patients as not trustworthy and violent (Kumpula et al, 2019).…”
Section: Resultsmentioning
confidence: 80%
“…Kumpula et al. (2019) also observed that care staff talked about themselves as parents and that they mobilised correction, discipline and control as tools for use in caring for patients. However, such limits always concern more than the behaviour of patients, because, as Butler (2007) has stressed, staff are also performing masculinity, especially a type of masculinity that prioritises acting with authority and purpose and, in that way, draws a line between rationality and madness, between “us” and “them” (Foucault, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Losing compassionate and empathetic nursing care when providing for patients with mental health problems in forensic settings can hinder the nurse-patient relationship by depersonalizing it [1]. Psychiatric forensic nursing involves complex relations between mental health care and the criminal justice system [2]. Often, forensics nurses care for those who have committed violent crimes.…”
Section: Introductionmentioning
confidence: 99%